Tying your enemy's hands in close races: The politics of federal transfers in Brazil - Fernanda Brollo; Tommaso Nannicini (Institute for the Study of Labor (IZA), 2011)
This paper uses a quasi-experimental strategy to disclose utterly political reasons behind the allocation of intergovernmental transfers in a federal state. We apply a regression discontinuity design in close elections to identify the effect of political alignment on federal transfers to municipal governments in Brazil. We find that municipalities where the mayor is affiliated with the coalition of the Brazilian President receive larger (discretionary) infrastructure transfers by about 40% in pre-election years. This effect is mainly driven by the fact that the federal government penalizes municipalities run by mayors from the opposition coalition who won by a narrow margin, thereby tying their hands for the next election.
urn:nbn:de:101:1-201105173341
Keywords: C21; D72; H77; 330; federal transfers; political alignment; regression discontinuity